Opini Audit, Ukuran Perusahaan, Dan Profitabilitas Terhadap Audit Delay - Rofiatul Lutfiah Ariany; Mulyaningtyas (Program Studi Akuntansi - STIE Kesuma Negara Blitar, 2023)
The goal of this study is to find out how audit delay is affected by company size, profitability, and audit opinion. Review delay is the time frame between the end date of the monetary year, to be specific December 31, to the date the review assessment is distributed in the review report. The examination populace is mining elements recorded on the Indonesia Stock Trade for the 2019-2021 period. The non-likelihood testing procedure utilizes a purposive inspecting strategy with a sum of 20 elements. The information investigation strategy utilized is numerous relapse examination. The consequences of the review show that organization size essentially affects review delay, implying that the bigger the organization size as estimated by the all out resources or abundance claimed by an element, the more complete the review report fruition time will be. Benefit and review assessment significantly affect review delay.